Heritage and globalisation - Labadi, Sophia; Long, Colin, 1966- (Milton Park, Abingdon, Oxon, England : Routledge, 2010)
This volume analyses the politics, policy and practice of cultural heritage at the global level, identifying the major directions in which international heritage practice is moving and exploring the key issues likely to shape the cultural heritage field in the 21st century.
The magic list of global issues : UNESCO, World Heritage and the agendas of states / Marc Askew -- Politics and power : the Hiroshima Peace Memorial (Genbaku Dome) as World Heritage / Olwen Beazley -- World Heritage, authenticity and post-authenticity : international and national perspectives / Sophia Labadi -- An ivory bull's head from Afghanistan : legal and ethical dilemmas in national and globalised heritage / Juliette van Krieken-Pieters -- Globalising intangible cultural heritage? : between international arenas and local appropriations / Chiara Bortolotto -- Heritage tourism : the dawn of a new era? / Tim Winter -- The globalisation of heritage through tourism : balancing standardisation and differentiation / Noel B. Salazar -- The business of heritage and the private sector / Fiona Starr -- Cultural heritage and the global environmental crisis / Colin Long and Anita Smith -- Conflict heritage and expert failure / Lynn Meskell -- Material heritage and poverty reduction / Kathryn Lafrenz Samuels.
Includes bibliographical references and index.
Keywords: Heritage tourism; Sustainable tourism; Culture and tourism; Culture and globalization; Cultural property -- Protection; Cultural property -- Management